2024
DOI: 10.1109/access.2024.3361407
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Robustness of IoT-Powered Smart City Applications Through Service-Reliant Application Authentication Technique

Jamil Abedalrahim Jamil Alsayaydeh,
Irianto,
Mohanad Faeq Ali
et al.

Abstract: In applications related to smart cities, the Internet of Things (IoT) promotes service scalability regardless of variations in user density. Many customers require several safety procedures to supply reliable and effective application services. Undependable user identity was the cause of the current case of Permanent Denial of Service (PDoS). The article discusses service-dependent application authentication (SRAA), a defense against PDoS attacks, in the context of smart cities. This authentication method uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Saleem et al ( 2023) suggested an Adaptive Information-Centric Network utilizing Edge Computing Framework (AICN-ECF) to improve data traffic control and security in smart cities [17], [18]. The technology enhances user experience by combining edge computing with information-centric networking to optimize content distribution and caching.…”
Section: Related Workmentioning
confidence: 99%
“…Saleem et al ( 2023) suggested an Adaptive Information-Centric Network utilizing Edge Computing Framework (AICN-ECF) to improve data traffic control and security in smart cities [17], [18]. The technology enhances user experience by combining edge computing with information-centric networking to optimize content distribution and caching.…”
Section: Related Workmentioning
confidence: 99%